Consumer behaviour towards branded rice and rice products in Thrissur District - Sangeetha P.R (Department of Rural Marketing Management, College of Co-operation, Banking and Management, 2002)
The study entitled "Consumer behaviour towards branded rice and rice products in Thrissur District" was undertaken with the following objectives: * To find out the share of branded rice and rice products in total rice and rice product consumption; * To examine the consumer behaviour towards branded varieties of rice and rice products; and To identify the factors influencing consumer choice. The study was conducted in three wards viz., Mission Quarters, West Fort and Wadakkechira Bus Stand Area of Thrissur Municipal Town (now part of the Corporation). The sample consisted of 200 households, which were selected proportionate to the total number of households in each selected ward. The study was based on primary data collected from the sample respondents (housewives) using a pre-tested structured schedule. Bivariate tables, Percentages, Preferential Ranking Method, Kendall' s Coefficient of Concordance, Satisfaction Index and Likert's Scale were empl?yed to analyse and interpret data. The study was an explorative search into the behaviour of the consumers towards branded rice, rice products and basmati rice. An attempt was also made to find out the share of brand users among the respondents and to identify the factors influencing consumer choice. Analysis of the socio-economic profile of the respondents revealed that majority of them preferred non-branded rice and home-made rice products irrespective of socio-economic differences. The preference towards branded rice and rice products was comparatively higher among the respondents with higher education and higher income. Similarly, compared to aged people, the share of